Can the Common Good Be Reduced to My Welfare or Done Together-With-Others? - Zaragoza, Maria Victoria Hernández (Journal of Leadership, Accountability and Ethics, 2021)
The common good as a universal value, analyzed at the individual and collective or social level, is found in the management of information and libraries. Three common trends are presented: welfare, progress/development and none of the above, by way of individual and collective reflection, regarding the transition at the beginning of 2021. To which horizon should we direct our attention based on what has been done and today’s reality? The choice is in the hands of each individual. The personal and individual position influences the performance directed or not towards the common good of a group or community of any size. The results impact the trajectory of the library and information professional: to fulfill for my welfare or to serve beyond myself.